Switching Between Second-Generation Antipsychotics in Patients with Schizophrenia and Schizoaffective Disorder: 10-Year Cohort Study in Brazil - Fulone, Izabela; Silva, Marcus Tolentino; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2021)
Objective: Switching between second-generation antipsychotics (SGAs) is a common clinical practice in the treatment of schizophrenia and schizoaffective disorders due to differences in the drugs’ tolerability and safety profiles as well as the challenge of obtaining an ideal response. However, the factors associated with SGA switching remain uncertain and related real-world data are scarce. The main objective was to identify the factors associated with the switching of SGAs in patients with schizophrenia or schizoaffective disorder. Methods: We conducted a retrospective cohort study of outpatients with schizophrenia or schizoaffective disorder, who were aged ≥ 18 years and received a SGA (clozapine, olanzapine, risperidone, quetiapine or ziprasidone) from a Brazilian pharmaceutical assistance program for at least 3 months. We identified SGA users from 2008 to 2017 by using a national administrative database (Ambulatory Information System-SIA/SUS). The factors associated with the switches were evaluated by Cox proportional hazards regression and adjusted for sex and age; the confidence interval was set at 95% (95% CI). Results: In total, 563,765 patients were included. Female sex, advanced age of ≥ 70 years, residence in the Brazilian northeast region, and the type of antipsychotic used were associated with an increased risk of switching (p<0.001). The incidence of switching ranged from 37.6/100 person-years for clozapine users to 58.2 /100 person-years for risperidone users. Compared to the adjusted hazard ratio, for clozapine users, the corresponding ratios for risperidone, ziprasidone, quetiapine and olanzapine were 1.59 (95% CI, 1.57 – 1.61), 1.41 (95% CI, 1.39 – 1.44), 1.25 (95% CI, 1.23 – 1.26) and 1.11 (95% CI, 1.10 – 1.12) respectively. Conclusions: The groups most susceptible to SGA switching in real-life setting were older individuals, women, and those living in the Brazilian northeast region. Risperidone was associated with the highest risk of switching and as expected, clozapine was associated with the lowest risk of switching than that associated with the other SGAs.